2013
DOI: 10.1111/tct.12051
|View full text |Cite
|
Sign up to set email alerts
|

Using Gagne’s theory to teach procedural skills

Abstract: Gagne's instructional events can produce an effective and comprehensive lesson plan for teaching procedural skills, preparing learners with various preferred learning styles to perform psychomotor skills competently in clinical practice. This lesson plan can be of use for both teachers and students across clinical specialties, encouragingly outlining how Gagne's systematic and widely referenced theory can be creatively and practically used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…The findings of this study are consistent with what has been reported about the use of Gagne's events of instruction in clinical teaching. 13,15 Other disciplines, such as psychology, have used Gagne's events routinely to enhance instruction. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are consistent with what has been reported about the use of Gagne's events of instruction in clinical teaching. 13,15 Other disciplines, such as psychology, have used Gagne's events routinely to enhance instruction. 16 …”
Section: Discussionmentioning
confidence: 99%
“…To aid a meaningful learning experience, I discuss these learning objectives with the students at this stage to ensure that they agree and understand why they are learning this [ 5 ]. For example, revealing the objectives sequentially enhances the opportunity to clarify each item before continuing to the next.…”
Section: Informing Learners Of Objectivesmentioning
confidence: 99%
“…Another educational approach used was Gagne's Conditions of Learning [8]. This theory has been applied to other areas of medical education [9,10].…”
Section: Introductionmentioning
confidence: 99%